Leveraging Circular Economy Transition to Achieve Resilient and Sustainable Supply Chains of the Future: A study of EEE Industry - Sandeep Sehgal; Shivani Bali; Angappa Gunasekaran; Matthew H. Roy; Ritika Gugnani (Sustainable Futures)
The substantial rise in the scale of electronic waste is a considerable concern for electrical and electronic equipment (EEE) manufacturers. Transition to Circular Economy (CE) is a strategic move to combat the challenge of e-waste generation. Traditional supply chains (SC) and operations were designed to support linear ‘take-make-waste’ models. To successfully transition to CE and achieve a resilient supply chain in the future with sustainable operations, organizations will have to reconsider their current business models, product designs, and supply chains. While previous studies have identified enabling factors for CE transition, limited research has examined it through the combined lens of enablers and levers. This study addresses this gap through a structured three-phase methodology. In phase 1, a structured literature review was conducted using Scopus, Web of Science, and relevant industry reports to extract potential enablers and levers. In phase 2, expert validation was performed through the Delphi technique. Further, in phase 3, the Grey-DEMATEL (Decision-making Trial and Evaluation Laboratory) technique was used to understand the importance and association among enablers and levers. The findings indicate that government intervention and Industry 5.0 are the top two cause group enablers, followed by a circular supply chain, which emerged as an essential lever of the CE transition. At the same time, financial investments, followed by competence & skill set building of the workforce, are the two effect group levers. By combining theoretical depth with practical validation, this study contributes a novel, practice-oriented framework for accelerating the CE transition within the EEE sector and advancing the development of resilient and sustainable supply chains of the future.